Propriedades termodinâmicas de buracos negros com métricas que violam a simetria de Lorentz - Gomes, Débora Aguiar (2018)
Hawking radiation has provided a new horizon in the study of black holes. Classically, black holes do not emit radiation, only absorb it. However, when it comes to a quantum mechanical approach, it is possible to show that black holes do emit radiation. Many methods have been developed to evaluate black hole thermodynamical properties. Among them, we can highlight a semi-classical method, known as quantum tunneling, which has been applied to many gravitational models with satisfactory results. In the Hawking radiation context, the Lorentz symmetry breaking (LSB) can provide interesting contributions in the Planck energy scale. In the literature, we find calculations of the thermodynamical properties of LSB Schwarzschild-like solutions, using the surface gravity. In this work, we present the first results obtained via quantum tunneling method for Schwarzschild-like models in which the Lorentz symmetry does not hold.